Expression of AEG-1 and p53 and their clinicopathological significance in malignant lesions of renal cell carcinomas: a microarray study - Erdem, Havva; Oktay, Murat; Yildirim, Umran; Uzunlar, Ali Kemal; Kayikci, M. Ali (Polish Journal of Pathology, 2013)
The aim of this study was to investigate the relationship of AEG-1 and p53 with the prognostic parameters of renal cell carcinoma (RCC). In this study, 50 paraffin blocks were histopathologically diagnosed at the Department of Pathology of the Medical Hospital of Duzce University, between 2005 and 2011. The cases consisted of 24 clear cell (CC) and 26 non-clear cell (NCC) RCC subtypes as follows: 24 (48%) clear cell RCC, 12 (24%) papillary RCC, 4 (8%) multilocular cystic RCC and 10 (20%) chromophobe RCC; none had sarcomatoid changes. By immunohistochemical analysis we investigated AEG-1 and p53 expression in carcinomas of the kidney, and by statistical analysis determined their relationship with clinicopathological parameters. Significant relationships were found between increasing tumor diameter and the increase of p53 (p = 0.028). In addition, p53 was significantly related to renal sinus invasion (p = 0.05) and Fuhrman grade (p = 0.026). There was a significant relationship between increased AEG-1 staining scores and CC and NCC carcinoma subtypes (p = 0.032), tumor capsule invasion (p = 0.01) and lymphovascular invasion (p = 0.015). There was also a significant correlation between tumor size and capsule and lymphovascular invasion (p = 0.02). We concluded that high AEG-1 and p53 expression correlates with the prognostic parameters in RCC patients, and in addition may be associated with tumor progression.